Emerging landscape of circFNDC3B and its role in human malignancies - Sun, Kai; Yao, Huibao; Zhang, Peizhi; Sun, Yanning; Ma, Jian; Xia, Qinghua (Frontiers in Oncology, 2023)
In recent years, more attention has been paid to expanding the abundance of Circular RNAs (circRNAs), while the circRNAs that have been found to have significant functions have not been studied in different diseases. CircFNDC3B is one of the most researched circRNAs generated from fibronectin type III domain-containing protein 3B (FNDC3B) gene. Accumulating researches have reported the multiple functions of circFNDC3B in different cancer types and other non-neoplastic diseases, and predicted that circFNDC3B might be a potential biomarker. Notably, circFNDC3B can play roles in different diseases by binding to various microRNAs (miRNAs), binding to RNA-binding proteins (RBPs), or encoding functional peptides. This paper systematically summarizes the biogenesis and function of circRNAs, reviews and discusses the roles and molecular mechanisms of circFNDC3B and its target genes in different cancers and non-neoplastic diseases, which will do favor to broaden our comprehension of the function of circRNAs and facilitate subsequent research on circFNDC3B.